(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
This study has been undertaken to investigate the isolation of EPEC strains associated with diarrhea in children under 5 years of age.Two hundred and seventy two samples from patients with diarrhoea were collected from two tertiary care hospital. Esch. coli was isolated and identified from all the 272 samples from the patients using standard microbiological techniques. EPEC strains were identified on the basis of presence of bundle forming pilus (bfpA) gene. Among 272 samples 20 (7.35%) isolates were identified as EPEC on the basis of presence of bfpA gene detected by polymerase chain reaction. Maximum bfpA gene carrying EPEC strains (10%) were identified from 0-12 months age group. Rapid and reliable detection of EPEC in children under 5 years of age is required for successful microbiological surveillance and for treatment of EPEC mediated diarrhoeal disease. J. Dhaka National Med. Coll. Hos. 2013; 19 (02): 32-35